Assessment of implementation of rural development projects through community development association (CDA) in Apete community, Ibadan, Nigeria (2021)
This study focused on the implementation of community development projects through Community Development Association (CDA) in Apete, Ibadan. Three specific objectives, each with corresponding research questions and hypothesis, guided the study. The study adopted descriptive survey research design. Tlie population for the study comprised 1025 landlords in Apete community, Ibadan. A sample size of 197 was purposively drawn for the study. The instrument for data collection was a 14 item structured questionnaire tagged "community development projects and Community Development Association Questionnaire (CDPCDAQ)" modeled on a four-point rating of; strongly agree (SA)_4, Agree (A)_3, Disagree (D)_2 and Strongly Disagree (SD)_1. The instrument was validated by experts in community development and evaluators at the Institute of Education. The instrument was subjected to reliability test and the reliability coefficient of 0.86 was obtained. The research questions 1 and 2 were answered using mean and Standard deviation while the hypothesis was tested using Pearson Product Moment Correlation (PPMC) analysis at 0.05 level of significance. The data analyzed revealed that the level of community development by the Community Development Associations in Apete, Ibadan was low (Mean=2.26). Challenges facing the Association included inadequate funding (Mean=3.44), misappropriation of funds (Mean=3.20), poor involvement of community members in development projects (Mean=3.23), poor leadership (Mean=3.60), lack of governmental support (Mean=3.50) and lack of trust by community members (Mean=3.56). The concludes that Community Development Association is a critical variable for community development. Based on the findings, it was recommended that Community Development Associations should be operated through good governance and they should be transparent in their dealings with all developmental projects. Also, government should release adequate funds for community projects from time to time